Unveiling Hidden Meanings: Implicature in Donald Trump’s 2017 UN General Assembly Address - Hsb, Nur Reski Amelia Pepin; Yasmin, Aulia; Khasanov, UsmonAli (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
Political discourse frequently employs implied meanings to convey ideological positions, authority, and persuasion in indirect ways. This study investigates the use of implicature in Donald Trump’s 2017 United Nations General Assembly Address, with a specific focus on identifying the types of implicature and explaining their pragmatic functions within a global diplomatic context. The research aims to reveal how implied meanings operate as strategic rhetorical tools in political communication. Using a descriptive qualitative approach, fifteen selected utterances from the speech were analyzed based on Grice’s (1975) theory of implicature, which categorizes implicature into Particularized Conversational Implicature, Generalized Conversational Implicature, and Conventional Implicature. The analysis reveals that Particularized Conversational Implicature is the most dominant type found in the speech, followed by Generalized Conversational Implicature and Conventional Implicature. This dominance indicates that the speaker heavily relied on contextual factors, shared political knowledge, and audience assumptions to convey criticism, warnings, and ideological stances implicitly rather than explicitly. The use of context- dependent implicature allows sensitive political messages, including threats and evaluations of other nations, to be communicated indirectly while maintaining diplomatic formality. These findings suggest that implicature plays a crucial role in shaping meaning, managing face, and influencing audience interpretation in international political discourse. This study contributes to the field of pragmatics and political discourse analysis by demonstrating how implicature functions as a strategic linguistic resource in high-level diplomatic speeches and by highlighting the importance of pragmatic interpretation in understanding political communication beyond literal meaning.